Effects of yttria content on the CMAS infiltration resistance of yttria stabilized thermal barrier coatings system. (15th April 2020) - Gomez Chavez, Juan J.; Naraparaju, Ravisankar; Mechnich, Peter; Kelm, Klemens; Schulz, Uwe; Ramana, C.V.
Abstract: The effects of YO1.5 doping in yttria-zirconia based thermal barrier coatings (TBCs) against CMAS interaction/infiltration are discussed. The TBCs with an YO1.5 content ranging from 43–67 mol.% (balance ZrO2 ) were produced by electron beam physical vapor deposition (EB-PVD) techniques. The results reveal a trend of higher apatite formation probability with the higher free YO1.5 available in the yttria-zirconia system. Additionally, the infiltration resistance and amount of consumed coating appears to be strongly dependent on the YO1.5 content in the coating. The thinnest reaction layer and lowest infiltration was found for the highest produced 67YO1.5 coating. Complementary XRD experiments with volcanic ash/YO1.5 powder mixtures with higher yttria contents than in the coatings (80YO1.5 and pure YO1.5 ) also showed higher apatite formation with respect to increasing yttria content. The threshold composition to promote apatite-based reaction products was found to be around 50YO1.5 in zirconia which was proved in the coatings and XRD powder experiments. An YO1.5 -ZrO2 -FeO-TiO2 bearing zirconolite-type phase was formed as a reaction product for all the coating compositions which implicates that TiO2 in the melt acts as a trigger for zirconolite formation. This phase could be detrimental for CMAS/volcanic ash infiltration resistance since it can be formed alongside with apatite which controls or limits the amount of Y 3+ available for glass crystallization. The Fe rich garnet phase containing all the possible elements exhibited a slower nucleation compared to apatite and its growth was enhanced with slow cooling rates. The implications of phase stability and heat treatment effects on the reaction products are discussed for tests performed at 1250 °C.